2010
DOI: 10.1051/0004-6361/201015232
|View full text |Cite
|
Sign up to set email alerts
|

Detection of nonthermal emission from the bow shock of a massive runaway star

Abstract: Context. The environs of massive, early-type stars have been inspected in recent years in the search for sites where particles can be accelerated up to relativistic energies. Wind regions of massive binaries that collide have already been established as sources of highenergy emission; however, there is a different scenario for massive stars where strong shocks can also be produced: the bow-shaped region of matter piled up by the action of the stellar strong wind of a runaway star interacting with the interstel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
150
1
17

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(174 citation statements)
references
References 20 publications
6
150
1
17
Order By: Relevance
“…Benaglia et al (2010) detected radio emission from the bow shock produced by the runaway star BD+43 3654, consistent with synchrotron radiation produced by the interaction of the relativistic electrons with the magnetic field of the acceleration region. Later, del Valle & Romero (2012) presented a nonthermal emission model that predicted the production of high-energy photons in these acceleration regions in sufficiently large numbers to be detected in X-rays.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…Benaglia et al (2010) detected radio emission from the bow shock produced by the runaway star BD+43 3654, consistent with synchrotron radiation produced by the interaction of the relativistic electrons with the magnetic field of the acceleration region. Later, del Valle & Romero (2012) presented a nonthermal emission model that predicted the production of high-energy photons in these acceleration regions in sufficiently large numbers to be detected in X-rays.…”
Section: Introductionmentioning
confidence: 63%
“…The most massive object is now seen as an O4If. BD+43 3654 has been reported to have formed a bow shock detected in the IR (Comerón & Pasquali 2007) and in radio (Benaglia et al 2010). These two observations are coincident and extensive.…”
Section: Bd+43 3654mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, this study does not concern massive X-ray and/or γ-ray binaries or microquasars that include a compact object (Fender & Maccarone 2004;Khangulyan & Aharonian 2005;Bosch-Ramon 2007;Bosch-Ramon & Rieger 2011) and is neither related to supernova remnants, known to be efficient particle accelerators (Romero 2004;Reynolds 2011;Vink 2013). Moreover, the class of objects debated does not include rapidlymoving runaway massive stars whose stellar wind interacts with the interstellar medium, producing strong shocks likely to accelerate particles (Benaglia et al 2010b;Romero et al 2011;Peri et al 2011;del Valle & Romero 2012).…”
Section: The Cataloguementioning
confidence: 99%
“…Benaglia et al (2010) have reported non-thermal radio emission from the bowshock of the runaway star BD +43 • 3654. This emission is thought to be synchrotron radiation generated by the interaction of relativistic electrons with the magnetic field of the source.…”
Section: Introductionmentioning
confidence: 99%